EKOLOGI GLOBAL DALAM FIQH BI’AH BERDASARKAN HADIS NABI - Achmad Mahbuby; Shofil Fikri; Khairul Umam (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
The global ecological crisis marked by deforestation, pollution, and climate change requires a religious paradigm that can provide ethical and normative solutions. The Hadith of the Prophet Muhammad SAW about the recommendation to plant trees even if the apocalypse is imminent is one of the prophetic texts that contains profound ecological messages. Global ecology, when analyzed from the perspective of Hadith, serves as a foundation for developing environmental jurisprudence (fiqh). To address this issue, a qualitative analysis is needed using a thematic approach (maudhu'i) to Hadiths related to ecology, supplemented by an examination of the chain of narration (sanad) and text (matan) to ensure their validity, as well as contextual analysis to reveal their relevance in contemporary contexts. The research findings indicate that the Hadith about planting trees until the apocalypse contains values of ecological optimism, sustainability, and Maqasid Al-Shariah, particularly in efforts to preserve the environment (Hifz Al-Bi'ah). This underscores that the Hadiths of the Prophet are not only a source of worship law but also a normative basis for environmental jurisprudence (fiqh) that is relevant to issues of climate change and nature conservation movements. Thus, these findings contribute theoretically to the development of green fiqh in contemporary Islamic studies and have practical implications for community-based ecological movements among Muslims.